Maple compounds prevent biofilm formation in Listeria monocytogenes via sortase inhibition - Elbakush, Ahmed M.; Trunschke, Oliver; Shafeeq, Sulman; Römling, Ute; Gomelsky, Mark (Frontiers in Microbiology, 2024)
The Pss exopolysaccharide (EPS) enhances the ability of the foodborne pathogen Listeria monocytogenes to colonize and persist on surfaces of fresh fruits and vegetables. Eradicating listeria within EPS-rich biofilms is challenging due to their increased tolerance to disinfectants, desiccation, and other stressors. Recently, we discovered that extracts of maple wood, including maple sap, are a potent source of antibiofilm agents. Maple lignans, such as nortrachelogenin-8’-O-β-D-glucopyranoside and lariciresinol, were found to inhibit the formation of, and promote the dispersion of pre-formed L. monocytogenes EPS biofilms. However, the mechanism remained unknown. Here, we report that these lignans do not affect Pss EPS synthesis or degradation. Instead, they promote EPS detachment, likely by interfering with an unidentified lectin that keeps EPS attached to the cell surfaces. Furthermore, the maple lignans inhibit the activity of L. monocytogenes sortase A (SrtA) in vitro. SrtA is a transpeptidase that covalently anchors surface proteins, including the Pss-specific lectin, to the cell wall peptidoglycan. Consistent with this, deletion of the srtA gene results in Pss EPS detachment from listerial cells. We also identified several additional maple compounds, including epicatechin gallate, isoscopoletin, scopoletin, and abscisic acid, which inhibit L. monocytogenes SrtA activity in vitro and prevent biofilm formation. Molecular modeling indicates that, despite their structural diversity, these compounds preferentially bind to the SrtA active site. Since maple products are abundant and safe for consumption, our finding that they prevent biofilm formation in L. monocytogenes offers a viable source for protecting fresh produce from this foodborne pathogen.